Registration of Six Germplasm Lines of Cotton with Resistance to the Root‐Knot and Reniform Nematodes. Issue 2 (27th April 2017) - McCarty, J. C.; Jenkins, J. N.; Wubben, M. J.; Hayes, R. W.; Callahan, F. E.; Deng, D.
Abstract : Six upland cotton ( Gossypium hirsutum L.) germplasm lines, M Rk‐Rn 1(Reg. No. GP‐1015, PI 678938), M Rk‐Rn 2 (Reg. No. GP‐1016, PI 678939), M Rk‐Rn 3 (Reg. No. GP‐1017, PI 678940), M Rk‐Rn 4 (Reg. No. GP‐1018, PI 678941), M Rk‐Rn 5 (Reg. No. GP‐1019, PI 678942), and M Rk‐Rn 6 (Reg. No. GP‐1020, PI 78943), with resistance to root‐knot nematode [ Meloidogyne incognita (Kofoid and White) Chitwood], and reniform nematode ( Rotylenchulus reniformis Linford and Oliveria) were jointly released by the USDA‐ARS and the Mississippi Agricultural and Forestry Experiment Station in 2016. The source of resistance to root‐knot nematode was M‐240 RNR (PI 592511) and to reniform nematode was M713 Ren1 (PI 665928). The two lines were crossed and plants were selected using markers with subsequent crosses to 'Sure‐Grow 747' (PI 656375), followed by marker selection. The germplasm lines were selected using simple sequence repeat (SSR) markers CIR 316 and BNL 3661 that are linked to root‐knot resistance and GH 132, BNL 3279, and BNL 569 that are linked to reniform resistance genes. Egg production of root‐knot and reniform nematodes was suppressed significantly from the susceptible check Sure‐Grow 747 in growth chamber tests. In addition to resistance to both nematodes, these lines, which also exhibit differences for agronomic and fiber traits such as length, strength, and micronaire, should be valuable to cotton breeding programs. The successful use of these specific SSR markers further validates their use in selection of nematode‐resistant plants in segregating generations.